Plan exportador de café procesado sostenible, café cristal ubicado en Circasia Quindío. (2013)
Within the scope of business development, this project is aimed at designing an exporting plan for the enterprise CAFÉ CRISTALES which produces each own brand of special coffees and which is located in CIRCASIA-QUINDÍO situated four thousand meters above the sea level. Through this research, there will be determined the stages to follow in the design of a exporting plan in an international market which will also be defined by means of a study of intelligence of markets. This type of research will be carried out in a descriptive aim by which it is intended to establish the demographic characteristics of the target population, its behavior and attitude toward the forth proposal determining the marketing, production, financial, and organizational aspects to carry out the exporting plan. In addition, such a plan is intended to assess needs, strengths and shortcomings of the enterprise and its product, special coffee CRISTALES, as well as the strategies and activities to run within a set time foretelling the exporting goals. The exporting plan of special coffees considers to be important the application of the theory of administration and the basic concepts that allow for strategic planning in business and international marketing. Finally, it is determined that the enterprise CRISTALES accounts for a thorough and defined process in harvesting, fruit-picking, as well as in packing and sales, meeting the standards required by the sealing certification which allows to portray a flawless and qualitative process toward the development of its productive activity and merchandising of special coffees.